2007
DOI: 10.1097/ta.0b013e31803245c7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Physician Staffing and Resource Allocation: Sine-Wave Variation in Hourly Trauma Admission Volume

Abstract: Trauma admissions conform to a sine-wave pattern with a 3.5-fold increase in admissions between morning and evening hours. This has significant implications for manpower and resource allocation with additional resources needed in the hours around 7:00 pm and later. Educational and administrative activities are best scheduled during low-volume morning hours. Nighttime admissions are higher risk and thus more likely to need senior-level expertise and consume hospital resources. Trauma centers should use these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Looking at hourly admission data from the United States National Trauma Data Bank, Vaziri et al 18 observed a sine-wave pattern in the number of patients admitted with a 3.5-fold increase in admissions in the evening hours, with a peak at 7:00 PM, compared with the morning hours. In a series of 9,408 traumas over 6 years, Bhattacharyya et al 19 found a significant relationship between weather and trauma center activity, with temperature and precipitation independently associated with trauma volume.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at hourly admission data from the United States National Trauma Data Bank, Vaziri et al 18 observed a sine-wave pattern in the number of patients admitted with a 3.5-fold increase in admissions in the evening hours, with a peak at 7:00 PM, compared with the morning hours. In a series of 9,408 traumas over 6 years, Bhattacharyya et al 19 found a significant relationship between weather and trauma center activity, with temperature and precipitation independently associated with trauma volume.…”
Section: Discussionmentioning
confidence: 99%
“…The only data are from the study by Vaziri et al using the US NTDB, which observed an increase in the ISS of trauma admissions in the early hours. 34 The increased injury severity seen in the early hours may be due to an increased severity of RTCs during this time, with driving speed, alcohol use and fatigue all thought to contribute. 30,35 Further analysis of the mechanism of injury associated with the BSUH admissions would be required for any conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Emergencies occur without regard for time and require an on-call team to manage them at all hours 2 . The emergent diagnoses may not be straightforward due to confounding of co-morbidities that cannot be optimized prior to operation.…”
Section: Introductionmentioning
confidence: 99%